Asbestos Disaster Lessons from Japan$1 (Bs Experience /s - Miyamoto, Kenichi; Morinaga, Kenji; Mori, Hiroyuki; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2011)
Japan$1 (Bs asbestos disasters, encompassing both occupational disease and environmental pollution, have been caused principally by the asbestos textile, asbestos cement water pipe, and construction industries. This book is unique in its interdisciplinary approach to those disasters as it incorporates medical science, economics, political science, law, architecture, environmental engineering, sociology, and journalism. Written by authorities in their fields, the chapters reflect the integration of these disciplines in topics that include a historical review of asbestos issues in Japan, asbestos-related diseases, international aspects of the asbestos industry, public policy, divisions of responsibility, relief activities in emergencies, and countermeasures enacted by local governments. The lessons of asbestos problems and policies in Japan are particularly important for developing countries to prevent the proliferation of asbestos disasters. This volume serves as a textbook on asbestos issues for all countries, especially where there is widespread use of asbestos.s
Keywords: Environmental sciences; Medicine; Epidemiology; Environmental Medicine; Social sciences; Environment; Environmental Health; Medicine/Public Health, general; Epidemiology; Political Science, general; Social Sciences, general